A) x + x/2 + x/3 = 42 B) x + y + z = 42 C) x + 2x + 3x = 42 D) x + x + 2 + x + 3 = 42
A) x + x + 1 + x + 2 = 61 B) a + y + z = 61 C) x + x + x = 61 D) x + 2x + 3x = 61
A) x2 B) 2x C) x/2 D) x+x
A) a - b2 B) (a - b)2 C) a2 - b2 D) a2 - b
A) x + x / 3 B) 3x + x / 3 C) 3x - x / 3 D) x - x / 3
A) x + 1 B) x2 C) 1 / x D) x
A) c2 = a2 - b2 B) c2 = a2 b2 C) c2 = a2 + b2 D) c2 = a + b
A) 5a B) 5 - a C) a - 5 D) a + 5
A) (a + b) / (a - b) B) (a + b) - (a - b) C) (a + b)(a - b) D) (a + b) + (a - b)
A) 2x - y B) x - 2y C) -2xy D) 2xy
A) xy = 45 B) x + y = 45 C) x / y = 45 D) 2x + y = 45
A) A = 2(b +h) B) A = (b -h) / 2 C) A = bh / 2 D) A = (b +h) / 2
A) x2 B) x - 2 C) 2x D) 2 + x
A) (x - y - z) / 3 B) (x + y + z) / 3 C) 3(x + y + z) D) x + 2y + 3z
A) P = 4 - a B) P = a2 C) P = 4a2 D) P = 4a
A) n - 3 B) n3 C) 3n D) 3n3
A) x(x - y) B) xy C) (x + y)(x - y) D) (x+y) - (x - y)
A) 3a - b B) 3(a - b) C) a - 3b D) (a - b)3
A) x - 3 = 19 B) x3 = 19 C) x + 3 = 19 D) 3x = 19
A) g / f B) g - f C) g + f D) gf
A) h + k B) h / k C) h - k D) hk
A) b - c B) b + c C) bc D) b / c
A) (abc)4 B) (abc)2 C) (2abc)2 D) 2(abc)2 |